1993
DOI: 10.1007/bf01244916
|View full text |Cite
|
Sign up to set email alerts
|

Development of tolerance to anxiolytic effects of chlordiazepoxide in elevated plus-maze test and decrease of GABAA receptors

Abstract: Repeated administration of benzodiazepines has been reported to produce tolerance in animals and humans. Using an elevated plus-maze test and an autoradiographic technique, we investigated whether repeated administration of chlordiazepoxide produced tolerance to its anxiolytic effects, and whether such repeated administration altered benzodiazepine and GABAA receptors. Tolerance to the anxiolytic effect of chlordiazepoxide was produced when it was administered at a dose of 30 mg/kg (i.p.) once a day for 10 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Also, while chronic DZ-treated animals had significantly lower closed arm entries than vehicle animals, this finding was not observed with center square time (Fernandes and File 1996). Previous research has reported that the dose and the duration of BZ exposure may play a role in the detection of tolerance to the anxiolytic effects of the BZs (File 1989a;Chopin et al 1993;Ishihara et al 1993). The DZ implants used in the present study produce continuous exposure to low levels of drug that are equivalent to a cumulative dose of 5 mg/kg of DZ per day (Gallager et al 1985).…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Also, while chronic DZ-treated animals had significantly lower closed arm entries than vehicle animals, this finding was not observed with center square time (Fernandes and File 1996). Previous research has reported that the dose and the duration of BZ exposure may play a role in the detection of tolerance to the anxiolytic effects of the BZs (File 1989a;Chopin et al 1993;Ishihara et al 1993). The DZ implants used in the present study produce continuous exposure to low levels of drug that are equivalent to a cumulative dose of 5 mg/kg of DZ per day (Gallager et al 1985).…”
Section: Discussionmentioning
confidence: 44%
“…Using anti-conflict tests, a lack of tolerance to the anxiolytic effect following chronic exposure to a variety of BZs has been shown (Margules and Stein 1968;Cook and Sepinwall 1975;McMillan and Leander 1978). More recent studies using the elevated plus-maze, conditioned defensive burying and the social interaction test have shown that chronic exposure reduces the anxiolytic effects of the BZs tested (Vellucci and File 1979;Stephens and Schneider 1985;Treit 1985b;File 1989aFile , 1989bIshihara et al 1993;Brett and Pratt 1995). These contradictions suggest that procedural differences and the behavioral test used to measure anxiety may affect the demonstration of tolerance following chronic benzodiazepine exposure.…”
Section: Introductionmentioning
confidence: 87%
“…In addition, GABAa receptor inverse ago nists are known to suppress alcohol drinking in selectively bred alcohol-preferring (P) rats [18,24,25,28], These observations are consistent with the notion that the cen tral GABA system is involved in regulating alcohol prefer ence [13,29]. Since the benzodiazepine inverse partial agonist RO 15-4513 interacts with the GABAa receptor complex to exert its alcohol-antagonistic properties [54], it is conceivable that the reinforcing effect of ethanol [53] is mediated, in part, through GABAa receptors [34,55], Given the role of GABAa receptors in anxiety [15] and the studies showing an anxiolytic effect of ethanol on anxious P rats [52], it appears that the GABA system is likely to be involved in both alcohol preference and anxiety. In order to understand a possible association of GABA receptors with alcohol preference, this study was designed to exam ine whether there is an innate difference of GABAa recep tors in the brains of rats selectively bred for high and low alcohol preference.…”
supporting
confidence: 73%
“…Interestingly, we have observed similar changes (reduction of [3H]muscimol binding but no change in [3H]flunitrazepam binding) in mice that had acquired tolerance to the anxiolytic effects of chlordiazepoxide (9). Therefore, we consider that be havior indicating anxiety in aged rats, which includes decreases in time spent in social interaction between pairs from different cages and increases in starting latency, defe cation and urination in an open field, may be related to a reduced number of GABAA receptors in the brain.…”
Section: Methodssupporting
confidence: 53%